2005
DOI: 10.1080/00420980500035261
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Planning on Local Business Rents

Abstract: Despite the pervasiveness of planning intervention in the land and property market, the economic effects of the planning system have been little researched. While there is a growing body of work addressing this issue in the housing sector, similar work considering the business sector is marked only by its absence. The paper describes the first substantive attempt to explore this subject area through an analysis of the impact of planning on business rents. A full structural model of a local property market was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Besides, location choices of private economic activities exert important constraints upon urban land rent (LaFountain, 2005), and on offices prices (Henneberry et al, 2005). Although computation of the impacts exerted by different variables on offices prices is straightforward Jones, 1998, 2002;Nappi-Choulet et al, 2007;Nitsch, 2006), the same does not necessarily hold true for land values, because political, economic and psychological factors, together with property rights and planned uses and regulations mingle altogether and strongly impact on their values.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, location choices of private economic activities exert important constraints upon urban land rent (LaFountain, 2005), and on offices prices (Henneberry et al, 2005). Although computation of the impacts exerted by different variables on offices prices is straightforward Jones, 1998, 2002;Nappi-Choulet et al, 2007;Nitsch, 2006), the same does not necessarily hold true for land values, because political, economic and psychological factors, together with property rights and planned uses and regulations mingle altogether and strongly impact on their values.…”
Section: Discussionmentioning
confidence: 99%
“…Henneberry et al (2005) identified the concept of agglomeration economies as an important link between urban theory and property economics. Their study suggested that the locational concentration of all three major commercial property sectors (offices, retail and industrial) plays a role in the determination of business rents.…”
Section: Theory and An Empirical Modelmentioning
confidence: 99%
“…Henneberry et al (2005) develop a multi-equation model of rental values and development activity in an attempt to isolate the impact of planning constraints from other economic drivers of property values. The relative constraint imposed by local planning regimes is proxied by the proportion of applications approved.…”
Section: Planning Policy Change and The Workings Of The Retail Propermentioning
confidence: 99%